Seismic vulnerability of masonry churches in Abruzzi region, Italy. (August 2021) - Zizi, Mattia; Corlito, Valentina; Lourenço, Paulo B.; De Matteis, Gianfranco
Abstract: In the current paper, a study aimed at assessing the seismic vulnerability at a regional scale of existing masonry churches based on a typological methodology is proposed. In particular, the study refers to the Abruzzi, which is an Italian region affected by a significant seismic hazard. Firstly, an accurate historical and typological characterization aimed at identifying the most widespread church typologies in this area is proposed. Hence, six main church samples have been defined based on recurrent geometrical and constructive features, namely two Medieval and four post-Medieval church types. Then, by adopting common assumptions for the definition of both geometries and mechanical characteristics of the masonry, numerical analyses have been carried out. To this purpose, six FEM Models have been implemented in order to operate specific comparisons between the analysed churches. In particular, a mass-proportional distribution of forces has been adopted and the attainment of the Damage Limit State for Artistic Asset (SLA) has been assessed. Despite the simplified hypotheses, the analysis has provided a good correspondence with damage scenario observed in churches that experienced the recent seismic events occurred in this area (i.e. L'Aquila 2009 and Central-Italy 2016–17). Moreover, the conducted comparison lays the groundwork for predictive aims and confirms that Italian post-Medieval churches are generally characterized by a higher vulnerability than the Medieval ones.